Indonesian language policy and the views of language teachers in Yogyakarta: Implications for action - Suwarno, Bambang (Curtin University, 2014)
This study critically examined Indonesian language policy and planning (ILPP) together with the views of Javanese language teachers of the impact of ILPP on heritage languages and the implications for policy review. It was found that ILPP might not be effective to stem language shift or be congruent with the Indonesian Constitution. Models were conceived for policy revision, one from the teachers’ views while another from language policy theory and Indian language policy.